KEMAMPUAN GURU-GURU MENERAPKAN PENDEKATAN SAINTIFIK DALAM PENGEMBANGAN KETERAMPILAN PROSES SAINS ANAK - Lolla Puspaning Tias, - (2017)
The background of this research explains the importance of children's science process skills which needs to be developed from an early age. It is also necessary to apply proper learning approaches such scientific approach. The purpose of this research is to determine the ability of teachers in applying a scientific approach in the development of science process skills in early childhood in TK Negeri Centeh, Bandung. This research applies the qualitative descriptive method and the technique of collecting data is done by interviews, observations, and documentary analysis. The result of this research shows that the ability of teachers to apply scientific approach in the development of science process skills in TK Negeri Centeh is good, assessed from; 1) the ability of teachers to apply the scientific approach include: the plans, purposes, principles, processes and tools/media used in applying the scientific approach are well structured, 2) the application of the scientific approach to early childhood's process skills is implemented as planned include: the steps of application, tools/media used, success criteria, and assessment of the development of science process skills in early childhood, 3) the factors that affect the application of scientific approach to early childhood's process skills include: the preparation of the learning environment, implementation of learning, and assessment of learning, 4) the problems faced in the application of scientific approach to early childhood's process skills handled directly by the teacher when the problems appear when the implementation of learning. The skills of science process in TK Negeri Centeh can be developed influenced by the mastery of teachers in applying scientific approach to science process skill learning.---- Penelitian ini dilatarbelakangi oleh pentingnya keterampilan proses sains anak yang perlu dikembangkan dari usia dini dan dibutuhkan penerapan pendekatan pembelajaran yang tepat untuk memenuhi hal tersebut. Salah satunya adalah dengan menerapkan pendeketan saintifik. Adapun tujuan dari penelitian ini adalah untuk mengetahui kemampuan guru dalam menerapkan pendekatan saintifik dalam pengembangan keterampilan proses sains anak di TK Negeri Centeh Bandung. Metode yang digunakan dalam penelitian ini adalah studi deskriptif kualitatif di TK Negeri Centeh Bandung. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan studi dokumentasi. Hasil penelitian menunjukakan bahwa kemampuan guru dalam menerapkan pendekatan saintifik dalam pengembangan keterampilan proses sains anak di TK Negeri Centeh Bandung masuk pada kriteria baik, dilihat dari: 1) Perencanaan pembelajaran dilakukan melalui pembuatan Program Tahunan hingga Rencana Pelaksanaan Pembelajaran Harian (RPPH), 2) Pelaksanaan pembelajaran sesuai dengan yang direncanakan, guru menyajikan materi yang sesuai dengan tema, menggunakan media yang konkret dan menarik, serta menstimulasi anak dalam kegiatan saintifik yang dapat mengembangkan keterampilan proses sains anak, 3) Penilaian keterampilan proses sains anak yang dilakukan guru dengan menggunankan pengamatan secara langsung, catatan harian, dan disesuaikan dengan indikator yang telah ditetapkan. Keterampilan proses sains anak di TK Negeri Centeh Bandung dapat berkembang sesuai yang diharapkan, salah satunya dipengaruhi oleh penguasaan guru dalam menerapkan pembelajaran pendekatan saintifik terhadap keterampilan proses sains anak.